Email issue for working at information technology field - Xavier, Idva Maria Das Dores Gomes (International research journal of management, IT and social sciences, 2015)
The research was intended to know how matter of email function in working. Email has been used, when the first time everyone starts to the used internet. And email also one of the social media that have in that time. Agree with the expansion of the internet, have a lot of people that use email to make a communication with the other people. One of the ways that make everyone happy to use email is easy to sending information and easy to use. Email afoot from optional communication to essential. This is proved if we see the work ethic in the big/great city. Every day and every time they can’t stop to open their computer to check out their account email. Because they use to make a business communication from email. One of the most popular applications in the mobile devices is an email client.